2009
DOI: 10.2105/ajph.2007.132597
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With the Sexual Behavior of Canadian Aboriginal Young People and Their Implications for Health Promotion

Abstract: Objectives. We examined factors associated with having ever had sex, having more than 1 lifetime sexual partner, and condom nonuse at last incident of sexual intercourse among Canadian Aboriginal young people. Methods. We conducted a secondary analysis of data from the 2003 British Columbia Adolescent Health Survey, a cross-sectional survey of young people in grades 7 through 12. Results. Of 1140 young Aboriginal men, 34% had ever had sex; of these, 63% had had more than 1 sexual partner, and 21% had not use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 36 publications
4
29
0
Order By: Relevance
“…To ensure independence of data, we excluded older data [17,18]. Likewise, we included a study of the entire sample from the 2003 British Columbia Adolescent Health Survey [19], and excluded two articles [20,21] that analyzed a subsample of Aboriginal teens from the same survey. Consequently, nine articles were analyzed in the current study, with 10 independent data sources [4,15,16,19,[22][23][24][25][26].…”
Section: Selection Of Primary Studiesmentioning
confidence: 99%
“…To ensure independence of data, we excluded older data [17,18]. Likewise, we included a study of the entire sample from the 2003 British Columbia Adolescent Health Survey [19], and excluded two articles [20,21] that analyzed a subsample of Aboriginal teens from the same survey. Consequently, nine articles were analyzed in the current study, with 10 independent data sources [4,15,16,19,[22][23][24][25][26].…”
Section: Selection Of Primary Studiesmentioning
confidence: 99%
“…Behaviour change interventions need to move beyond the individual to address interpersonal, social, environmental, cultural and structural factors, which can be potent forces in prevention efforts (Devries et al 2009;Kaufman et al 2007a;Wilson & Miller 2003). Numerous studies have found that health and wellbeing are integrally connected to culture (Fagan & McDonell 2010;Kaufman et al 2007b;Leston, Jessen & Simons 2012;MooneySomers et al 2012;Ricci et al 2009;Rushing & Stephens 2012;Wilson & Miller 2003), and this is especially true for Indigenous communities where culture and language act as buffers/protective factors against negative effects of risk (McIvor et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The unresolved pain that manifested through cycles of historical and intergenerational trauma has resulted in high rates of sexual abuse within indigenous communities (Milloy, 1999;Provincial Health Officer, 2009). A history of sexual abuse is a known marker of reduced self-determination (Beitchman et al, 1992;Briere & Elliot, 1994;Devries, Free, Morison, & Saewyc, 2009) and is linked to increased vulnerability to HIV infection, therefore rendering victims even further vulnerable to AIDS-related disparities (Braitstein et al, 2003;Cunningham, Stiffman, Dore, & Earls, 1994;Miller, 1999;Whetton et al, 2006).…”
Section: Introductionmentioning
confidence: 99%